Pengaruh Efektivitas dan Kontribusi Pajak Bumi dan Bangunan terhadap Efektivitas Pendapatan Asli Daerah - Dea Elviana Dora; Diamonalisa Sofianty (UNISBA Press, 2022)
Abstract. The enactment of Law No. 28 of 2009 concerning regional taxes and regional levies forming a Land and Building Tax bill is under the authority of the Regional Government, thus it is very necessary to increase the realization of tax recipient targets, especially regarding Land and Building Tax. This requirement will encourage the Regional Government to further explore the potential of Regional Original Income from the Land and Building Tax sector in its territory. The title of this research is